Lipid Accumulation Product is Related to Metabolic Syndrome in Women with Polycystic Ovary Syndrome - Xiang, S.; Hua, F.; Chen, L.; Tang, Y.; Jiang, X.; Liu, Z. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Metabolic disturbances are common features of polycystic ovary syndrome (PCOS), which possibly enhance the risk of diabetes and cardiovascular disease. Lipid accumulation product (LAP) is an emerging cardiovascular risk factor. The aim of this study was to explore the ability of LAP to identify metabolic syndrome (MS) in PCOS women.In a cross-sectional study, anthropometric, biochemical and clinical parameters were measured in 105 PCOS women. Receiver operating characteristic (ROC) analysis was used to find out the cut-off points of LAP to predict MS. MS was categorized according to International Diabetes Federation (IDF) criteria.The prevalence of MS was 43.8% in this study. PCOS women with MS had significantly higher LAP levels compared to those without MS. LAP was highly correlated with components of MS. ROC analysis showed that LAP was a significant discriminator for MS in PCOS women, and the optimal cutoff point of LAP to predict MS was 54.2 (93.3% sensitivity, 96.7% specificity).LAP seems to be associated with MS and has a strong and reliable diagnostic accuracy for MS in PCOS women.
Keywords: polycystic ovary syndrome; metabolic syndrome; lipid accumulation product